Phylogenetic revision of the floricolous longhorn beetle genus Strangalidium Giesbert (Coleoptera: Cerambycidae). Issue 1 (2nd January 2020) - Gutiérrez, Nayeli; Noguera, Felipe A.; Zaragoza-Caballero, Santiago; Morrone, Juan J.
Abstract : The Central American genus Strangalidium Giesbert, 1997 is part of the subfamily Lepturinae, known for the floricolous habits of its species. A phylogenetic analysis was conducted to study the relationships of the species of the genus and other taxa that have been recognized as closely related to it. This study is the first that integrates characters codified with geometric morphometric methods for inferring the phylogeny of any group of Cerambycidae. In our results, Strangalidium is recovered as paraphyletic, forming a clade with Strangalia Dejean. Both genera are synonymized, and the species previously known as Strangalidium, herein transferred to Strangalia, are redescribed. One new species is described from Mexico: Strangalia giesberti sp. nov. from Chiapas. In addition, a key to identify the species is provided. http://zoobank.org/urn:lsid:zoobank.org:pubB8334A76-892D-4E82-900A-58DF02CBCD72 http://zoobank.org/urn:lsid:zoobank.orgact:54B9E3B7-1415-4AF1-8543-A3AEBE34B214